2013
DOI: 10.1101/lm.032052.113
|View full text |Cite
|
Sign up to set email alerts
|

DREAM/calsenilin/KChIP3 modulates strategy selection and estradiol-dependent learning and memory

Abstract: Downstream regulatory element antagonist modulator (DREAM)/calsenilin(C)/K+ channel interacting protein 3 (KChIP3) is a multifunctional Ca 2+ -binding protein highly expressed in the hippocampus that inhibits hippocampus-sensitive memory and synaptic plasticity in male mice. Initial studies in our lab suggested opposing effects of DR/C/K3 expression in female mice. Fluctuating hormones that occur during the estrous cycle may affect these results. In this study, we hypothesized that DR/C/K3 interacts with 17b-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In fact, previous studies in Kcnip3 -/- mice demonstrated that they have slightly increased anxiety levels compared to the wild-type controls, and no significant difference was observed compared to the wild-type control (Alexander et al, 2009). Another study in female Kcnip3 -/- mice also showed that the Kcnip3 gene deletion did not affect the anxiety level in the ovariectomized mice receiving or not receiving estradiol injections (Tunur et al, 2013). However, both our studies from elevated plus maze and open field tests indicated that Kcnip3 -/- rats had a higher anxiety level compared to the wild-type rats post CFA injection.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, previous studies in Kcnip3 -/- mice demonstrated that they have slightly increased anxiety levels compared to the wild-type controls, and no significant difference was observed compared to the wild-type control (Alexander et al, 2009). Another study in female Kcnip3 -/- mice also showed that the Kcnip3 gene deletion did not affect the anxiety level in the ovariectomized mice receiving or not receiving estradiol injections (Tunur et al, 2013). However, both our studies from elevated plus maze and open field tests indicated that Kcnip3 -/- rats had a higher anxiety level compared to the wild-type rats post CFA injection.…”
Section: Discussionmentioning
confidence: 98%
“…DREAM is mainly expressed at the presynaptic level in neurons [36], where it participates in the regulation of glutamate release in the synaptic cleft [37] and plays a role in hippocampus-sensitive memory and synaptic plasticity [38][39][40]. In addition, DREAM binds to the NR1 subunit of the main receptor involved in synaptic plasticity, NMDAR, causing a reduced surface expression of this ligand-gated ion channel and, ultimately, a decrease in NMDAR-mediated currents [31].…”
Section: Physiological Roles Of Dream In Cnsmentioning
confidence: 99%
“…In addition, resveratrol reduced the expressions of Aβ and ERβ, as well as increasing the expressions of choline acetyltransferase (ChAT), estradiol, and both the protein and mRNA of Erα [ 104 ]. Significantly, it is suggested that female sex hormones positively correlate with the improvement of cognitive functions and memory, and the increased secretion of neurotransmitters indirectly affects synaptogenesis [ 105 , 106 , 107 ]. Another study in vitro showed that the inhibition of Aβ aggregation by resveratrol (100 µM) was achieved by regulating the following proteins involved in proteostasis: ubiquitin-like protein (UBL) and X-box 1 binding protein (XBP-1) [ 108 ].…”
Section: Flavonoidsmentioning
confidence: 99%